Effects of long-term weekly iron and folic acid supplementation on lower genital tract infection – a double blind, randomised controlled trial in Burkina Faso - Loretta Brabin; Stephen A. Roberts; Sabine Gies; Andrew Nelson; Salou Diallo; Christopher J. Stewart; Adama Kazienga; Julia Birtles; Sayouba Ouedraogo; Yves Claeys; Halidou Tinto; Umberto d’Alessandro; et al. (BMC Medicine, 2017)
Abstract Background Provision of routine iron supplements to prevent anaemia could increase the risk for lower genital tract infections as virulence of some pathogens depends on iron availability. This trial in Burkina Faso assessed whether weekly periconceptional iron supplementation increased the risk of lower genital tract infection in young non-pregnant and pregnant women. Methods Genital tract infections were assessed within a double blind, controlled, non-inferiority trial of malaria risk among nulliparous women, randomised to receive either iron and folic acid or folic acid alone, weekly, under direct observation for 18 months. Women conceiving during this period entered the pregnancy cohort. End assessment (FIN) for women remaining non-pregnant was at 18 months. For the pregnancy cohort, end assessment was at the first scheduled antenatal visit (ANC1). Infection markers included Nugent scores for abnormal flora and bacterial vaginosis (BV), T. vaginalis PCR, vaginal microbiota, reported signs and symptoms, and antibiotic and anti-fungal prescriptions. Iron biomarkers were assessed at baseline, FIN and ANC1. Analysis compared outcomes by intention to treat and in iron replete/deficient categories. Results A total of 1954 women (mean 16.8 years) were followed and 478 (24.5%) became pregnant. Median supplement adherence was 79% (IQR 59–90%). Baseline BV prevalence was 12.3%. At FIN and ANC1 prevalence was 12.8% and 7.0%, respectively (P < 0.011). T. vaginalis prevalence was 4.9% at FIN and 12.9% at ANC1 (P < 0.001). BV and T. vaginalis prevalence and microbiota profiles did not differ at trial end-points. Iron-supplemented non-pregnant women received more antibiotic treatments for non-genital infections (P = 0.014; mainly gastrointestinal infections (P = 0.005), anti-fungal treatments for genital infections (P = 0.014) and analgesics (P = 0.008). Weekly iron did not significantly reduce iron deficiency prevalence. At baseline, iron-deficient women were more likely to have normal vaginal flora (P = 0.016). Conclusions Periconceptional weekly iron supplementation of young women did not increase the risk of lower genital tract infections but did increase general morbidity in the non-pregnant cohort. Unabsorbed gut iron due to malaria could induce enteric infections, accounting for the increased administration of antibiotics and antifungals in the iron-supplemented arm. This finding reinforces concerns about routine iron supplementation in highly malarious areas. Trial registration Trial registration number NCT01210040 . Registered with Clinicaltrials.gov on 27 September 2010